Efficiency measurement model of product based on non-parametric method - Ku-Mahamud, Ku Ruhana; Abdullah, Fader; Mat Kasim, Maznah; Abd Ghani, Nor Farzana; Ahmad, Faudziah (2010)
In the wake of the economic crisis, IT companies being totally dependent on project-based business, need to find ways to score higher profit with minimum resources usage. Measuring business performance and presenting the resulting information for action is one aspect of achieving business success. This paper presents an efficiency measurement model for products produced by organization that has been developed based on a non-parametric technique, called Data Envelopment Analysis. The model optimizes a ratio of multiple weighted outputs to a multiple weighted inputs, where the efficient unit will have a score of one, and the inefficient unit will have a score less than one. The model is simple and practical in implementation. It is hope that the projects which act as the decision making unit can later be used to determine the efficiency of the company department/unit that housed the projects. Projection for inefficient projects has also been provided.